PENGARUH STRATEGI REPOSITIONING HOLIDAY INN BANDUNG TERHADAP KEPERCAYAAN TAMU MEMBER - Shesarria, Gina; Siswhara, Gita (THE Journal : Tourism and Hospitality Essentials Journal, 2012)
Hospitality industry has three classifications of the National Chain Hotel, International Hotel Chain and hotels that are managed independently. International Hotel Chain is standing in Bandung one of them is the Holiday Inn. Holiday Inn Bandung is one of the four-star hotel which has the highest actual share best among customary international chain hotel in the city of Bandung. One of the guests that must be maintained is a guest member. The effort to maintain it is to make changes or repositioning. The purpose of this study was to obtain findings on repositioning strategies undertaken, the level of trust and influence of repositioning strategies undertaken Holiday Inn Bandung guest member of the trust. Repositioning strategy used theory is Muzellec Lambkin, whereas the theory of confidence used was Doney Canon. Objects in this study was the guest of a member who stays good corporate member guest and guest of individual members. Independent variable (X) is a repositioning strategy that consists of three dimensions of brand logos, building renovation and staff performance. Dependent variable (Y), namely trust. This type of study is a descriptive verifikatif, and the method used is survey with stratified random sampling technique, the obtained sample size of 100 respondents to the division of 56 respondents for this type of corporate members and 44 guests respondents for this type of individual member guest. Techniques of data analysis and hypothesis test used is multiple regression. The results showed that the repositioning strategy did have an influence on trust. Dimensional result greatest value of the brand logo of amounting to 5.742, then the second highest value obtained through the staff performance of 5.363, while the building renovation is considered guest members have no influence because the guest member has not felt comfortable and familiar with the appearance and location of new facilities.